Add the two equations together: (2x+y)+(x-y) = 1+8, so 3x = 9, x = 3. Then 2*3+y = 1 so y = -5.
Steve
2006-11-10 09:54:49
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
there's a couple different ways, the way I find easiest is to solve for one variable in terms of the other:
2x+y=1 and x-y=8 (I'll use the second one and x)
x-y=8 -- x=y+8
now put that into the other equation
2(y+8)+y=1
then solve for y
2y+16+y=1 -- 3y=-15 -- y=-5
then put that into an equation to solve for x (doesn't matter which equation)
x-(-5)=8 -- x=3
that gives you y=-5 and x=3 you can just insert them into the other equation if you have to check your work.
2006-11-10 17:58:52
·
answer #2
·
answered by NeRdYkId1101 3
·
0⤊
0⤋
by substitution: replace y by x - 8 in the first equation and then you will find 3x = 9 then x = 3 y = - 5
or by summing the two equations
there is a general algorithm called teh Gauss pivot to solve that kinf of system provided certain conditions
2006-11-10 17:56:28
·
answer #3
·
answered by jeff 1
·
0⤊
0⤋
2x+y=1
x-y=8
3x=9
x=3
These are called simultaneous equations the third line above is the sum of the first two equations eliminating y and getting a value for x
To find y sub x in to any of the equations
3-y=8
y=-5
2006-11-10 17:55:52
·
answer #4
·
answered by alanjb 1
·
0⤊
0⤋
2x+y=1
x-y=8
x=8+y
subsitute x to get
2(8+y)+y=1
16+2y+y=1
16+3y=1
3y=1-16
3y=-15
y= -5
then x should be
x-(-5)=8
x+5=8
x=8-5
x=3
2006-11-10 18:04:49
·
answer #5
·
answered by bu 1
·
0⤊
0⤋
2x+y=1
x-y=8
x=8+y
2(8+y)+y=1
16+2y+y=1
3y=-15
y=-5
x=8+(-5)
x=3
2006-11-10 17:54:14
·
answer #6
·
answered by bourqueno77 4
·
0⤊
0⤋
x-y=8
x=8+y
2x+y=1
2(8+y)+y=1
16+2y+y=1
16+3y=1
3y=1-16
3y=-15
y=-5
x-y=8
x--5=8
x=8-5
x=3
2006-11-10 18:02:17
·
answer #7
·
answered by Saphira 3
·
0⤊
0⤋